2003
DOI: 10.1107/s1600536803015186
|View full text |Cite
|
Sign up to set email alerts
|

3-(3,4-Dimethoxyphenyl)-1-(4-hydroxyphenyl)prop-2-en-1-one

Abstract: The title molecule, C 17 H 16 O 4 , is nearly planar, with a dihedral angle of 6.64 (6) between the two aromatic rings. The con®guration of the keto group with respect to the ole®nic double bond is s-cis. OÐHÁ Á ÁO and CÐHÁ Á Á% hydrogen bonds link the molecules to form layers parallel to the ab plane. The crystal structure is further stabilized by a number of CÐHÁ Á ÁO interactions, which form rings of R 1 2 (5), R 1 2 (6) and R 2 1 (5) graph set motifs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…1). A similar conformation has been reported previously for related structures (Ravishankar, Chinnakali, Nanjundan, Jone Selvamalar et al, 2003;Ravishankar, Chinnakali, Nanjundan, Radhakrishnan et al, 2003). The unsaturated ketone system is not strictly planar.…”
Section: Commentsupporting
confidence: 86%
“…1). A similar conformation has been reported previously for related structures (Ravishankar, Chinnakali, Nanjundan, Jone Selvamalar et al, 2003;Ravishankar, Chinnakali, Nanjundan, Radhakrishnan et al, 2003). The unsaturated ketone system is not strictly planar.…”
Section: Commentsupporting
confidence: 86%
“…For the background to chalcones, see: Awad et al (1960); Coudert et al (1988); Insuasty et al (1992Insuasty et al ( , 1997; Kolos et al (1996); Samshuddin et al (2010); Fun et al (2010); ; Shettigar et al (2010); Sharma et al (1997); Ravishankar et al (2003Ravishankar et al ( , 2005; Butcher et al (2006); Narayana et al (2007); Sarojini et al (2007a,b); Jasinski et al (2011). For bond-length data, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…Chalcones are also finding application as organic nonlinear optical materials (NLO) for their SHG conversion efficiency (Sarojini et al, 2006;Shettigar et al, 2010). The crystal structures of some of the related chalcones viz: 1-(3,4-dimethoxyphenyl)-3-(3-methylphenyl)prop-2-en-1-one (Sharma et al, 1997), 3-(3,4-dimethoxyphenyl)-1-(4-hydroxy-phenyl)prop-2-en-1-one (Ravishankar et al, 2003), 1-(4chlorophenyl)-3-(4-hydroxyphenyl)prop-2-en-1-one (Ravishankar et al, 2005) (Sarojini et al, 2007a,b) and (2E)-3-(2-anthryl)-1-(2-hydroxyphenyl)prop-2-en-1-one (Jasinski et al, 2011) have been reported. In a continuation of our studies of the structures of chalcones, we report the crystal structure of a new chalcone, (2E)-3-(3-benzyloxyphenyl)-1-(2-hydroxyphenyl)prop-2-en-1-one, C 22 H 18 O 3 , (I).…”
Section: S1 Commentmentioning
confidence: 99%
“…The molecular hyperpolarizability, , is strongly influenced, not only by the electronic effect, but also by the steric effect of the substituent (Cho et al, 1996). Crystal structures of similar compounds with a 4hydroxy group (Ravishankar et al, 2003), an 4-amino group (Selvi et al, 2003) or a 3-methyl group (Sharma et al, 1997) instead of a 4-fluoro group have been reported. Prompted by this and in a continuation of our quest to synthesize newer materials which can find use in the photonics industry, we have synthesized new chalcones and studied their SHG efficiency.…”
Section: Commentmentioning
confidence: 99%